2017
DOI: 10.3390/min7090174
|View full text |Cite
|
Sign up to set email alerts
|

Quartz-Amethyst Hosted Hydrocarbon-Bearing Fluid Inclusions from the Green Ridge Breccia in the Snoqualmie Granite, North Cascades, WA, USA

Abstract: Abstract:The Green Ridge Breccia cuts the composite Miocene Snoqualmie Batholith in King County, WA, USA. The granite was emplaced at~5 km depth between~17 and 20 Ma and the crosscutting NW trending breccia contains large angular blocks of the host granite (<1 m in longest dimension). The brecciated granite blocks are cemented by quartz-amethyst euhedra (<10 cm in longest dimension) bearing vugs. A notable feature is the presence of centimetric scale amber coloured oil inclusions within the quartz-amethyst cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
1
1
Order By: Relevance
“…This is in contrast to some other occurrences of oil in fractured basement, where oil inclusions were entrapped in vein minerals (e.g. Feely et al 2017;Parnell et al 2017c). The absence of oil inclusions in Cornwall implies that the ingress of oil occurred later than the youngest measured vein minerals (generally quartz in north-south crosscourses), although there is evidence of syn-oil mineralization at North Treskerby and Wheal Speed in intermixtures with ore minerals, and the oil represents a relatively late reactivation of fluid flow through the mineralized structures.…”
Section: Fluid Sourcecontrasting
confidence: 63%
“…This is in contrast to some other occurrences of oil in fractured basement, where oil inclusions were entrapped in vein minerals (e.g. Feely et al 2017;Parnell et al 2017c). The absence of oil inclusions in Cornwall implies that the ingress of oil occurred later than the youngest measured vein minerals (generally quartz in north-south crosscourses), although there is evidence of syn-oil mineralization at North Treskerby and Wheal Speed in intermixtures with ore minerals, and the oil represents a relatively late reactivation of fluid flow through the mineralized structures.…”
Section: Fluid Sourcecontrasting
confidence: 63%
“…Previous studies have reported that the typical silicate mineral quartz (SiO 2 ) was sometimes found with organic matters in its crystals as negative crystals and/or surface coating. Suchy et al discussed the formation sequences of organic inclusions in quartz obtained from the west region of the Czech Republic, analyzing by mass spectroscopic methods. However, the relationships between the states of organic inclusions in quartz and surrounding rocks were still unclear.…”
Section: Introductionmentioning
confidence: 99%